The Subject of Education: Disruptive Dilemma in Abraham Kuyper and Ellen White Thought - Halim Wiryadinata; Christar Arstilo Rumbay (Sekolah Tinggi Teologi Intheos Surakarta, 2020)
Abstract. The nature of education receives attention and public discussion as it is one dominant core of the cosmological system. However, it echoes to other public squares such as; the state, political power, culture, and religion, contains multi-layered of identity, and against a post-modernism era, which is a very disruptive period that could impact its nature. Abraham Kuyper is known as a public theologian, who offers wide works of education in Europe-Reformed tradition, while Ellen White, a central figure in American-Adventist, even worldwide, contributes unique perspectives. This article conducts qualitative research, attempts to interpret the works of Kuyper and White and reconstructs their idea in order to answer the intention of this research. Eventually, this essay shares the agreement between them concerning God's glorification and adoration as the intention of education, further, demonstrating the diversity where White maintains the holistic approach of education in which Kuyper against it. Moreover, this research attempts to uncover how both figures define the role of state over education.